Oxidative stress—A key determinant of complications and negative outcome in hepatitis E virus infected pregnancies: A comprehensive account involving cases from northeast India - Kashyap, Natasha; Islam, Mafidul; Kaur, Harpreet; Tiwari, Diptika; Begum, Anjuma; Bose, Moumita; Das, Chandana Ray; Saikia, Anjan Kumar; Kalita, Pankaj; Bose, Purabi Deka; Bose, Sujoy (Journal of medical virology, 2023)
Regulated oxidative stress (OS) is important during pregnancy. Sporadic studies suggest the significance of deregulated OS in hepatitis E virus (HEV) infected pregnancy, but with limited reactive oxygen species (ROS) or antioxidant markers. The present novel study, therefore, aimed to evaluate the significance of ROS‐antioxidant imbalance and resulting altered OS in HEV infected pregnancy complications like preterm delivery (PTD) and outcome. Difference in serum levels of ROS and antioxidant panel of markers were evaluated by ELISA for HEV immunoglobulin M RNA positive genotype 1 cases (including acute [acute viral hepatitis, AVH] and fulminant [fulminant hepatic failure, FHF] cases) and healthy term delivery subjects, and analyzed statistically. Direct ROS marker H2O2 levels and indirect OS marker for DNA damage 8‐hydroxy‐2′‐deoxyguanosine was significantly increased in HEV‐cases compared to controls, and was associated and prognostic factor for PTD and fetal death in HEV cases. A comparatively lower total serum antioxidant capacity was observed in the FHF cases compared to the control subjects and the AVH cases. Glutathione (GSH) levels and superoxide dismutase (SOD) activity were significantly associated with PTD in the FHF sub‐cohorts (p = 0.017) and AVH sub‐cohorts (p < 0.001), respectively, and was associated with poor prognosis in HEV cases. The serum H2O2 levels were found to be negatively correlated with SOD activity (p = 0.016) and GSH levels (p = 0.001) in the HEV‐AVH cases; and positively correlated with the viral load in HEV cases (p = 0.023). The ROS‐antioxidant imbalance resulting OS plays a detrimental associative role in HEV infected pregnancy complications like PTD and adverse pregnancy outcomes; and holds therapeutic significance.